What goes on when tertiary students are engaged in an online academic writing course? - Chan, Swee Heng; Han, Ai Leen (Penerbit UKM, 2005)
The learning process is a complex one with many intertwining variables. The learners’ characteristics could be a defining factor and so is prior learning experiences and knowledge, which are the manifests of metacognitive, socio-affective and cognitive systems. A learning task engagement calls for an exertion of personal control and the fulfillment of efficiency expectations. In learning, the learner activates a number of processes such as those that concern attentional, retrieval, metacognitive and rehearsal strategies. McCombs (1988) sums up these complexities in his multimodal model of learning with certain underlying assumptions. Among them is that learning success can be manipulated. In promoting learning, the teacher can promote strategy learning such as self-directed learning. Learners if trained can select and be their own judge as to the efficacy of strategy use for the learning task. Lessard-Closton (1997) identified several basic characteristics to describe language learning strategies: they are learner-generated, they enhance language learning and competence, they may be visible or unseen and they involve the processing of information and the use of memory.